The biological heterogeneity of oestrogen receptor positive breast cancer and its phenotypic characterisation - Habashy, Hany Onsy Fouad Ibrahim (2011)
Although global gene microarray studies have demonstrated the molecular heterogeneity of breast cancer (BC) and provided potential for clinical applications, the molecular subclassification of luminal/ER-positive tumours, which is the largest class of BC, remains unclear. Characterisation of luminal/ER-positive subtypes could have important implications in clinical decision-making and patient management.